Depolarization of mouse DRG neurons by GABA does not translate into acute pain or hyperalgesia in healthy human volunteers - Sohns, Kyra; Kostenko, Anna; Behrendt, Marc; Schmelz, Martin; Rukwied, Roman; Carr, Richard (PLOS ONE, 2024)
The majority of somatosensory DRG neurons express GABAA receptors (GABAAR) and depolarise in response to its activation based on the high intracellular chloride concentration maintained by the Na-K-Cl cotransporter type 1 (NKCC1). The translation of this response to peripheral nerve terminals in people is so far unclear. We show here that GABA (EC50 = 16.67μM) acting via GABAAR produces an influx of extracellular calcium in approximately 20% (336/1720) of isolated mouse DRG neurons. In contrast, upon injection into forearm skin of healthy volunteers GABA (1mM, 100μl) did not induce any overt sensations nor a specific flare response and did not sensitize C-nociceptors to slow depolarizing electrical sinusoidal stimuli. Block of the inward chloride transporter NKCC1 by furosemide (1mg/100μl) did not reduce electrically evoked pain ratings nor did repetitive GABA stimulation in combination with an inhibited NKCC1 driven chloride replenishment by furosemide. Finally, we generated a sustained period of C-fiber firing by iontophoretically delivering codeine or histamine to induce tonic itch. Neither the intensity nor the duration of histamine or codeine itch was affected by prior injection of furosemide. We conclude that although GABA can evoke calcium transients in a proportion of isolated mouse DRG neurons, it does not induce or modify pain or itch ratings in healthy human skin even when chloride gradients are altered by inhibition of the sodium coupled NKCC1 transporter.
Gesehen am 11.02.2025